(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2026)
This study examines the integration of Indian Knowledge Systems (IKS) into financial decision-making processes within the oil industry. Through qualitative analysis of case studies and existing literature, we demonstrate how traditional Indian principles like Dharma, Artha, and Nyaya can enhance corporate governance, risk management, and sustainability practices. The research reveals that while challenges exist in reconciling traditional wisdom with modern financial models, IKS offers valuable frameworks for ethical decision-making and long-term value creation. The paper concludes with practical recommendations for policymakers and corporate leaders seeking to harmonize traditional knowledge with contemporary business practices.